PENGARUH KEAMANAN KERJA DAN KEPEMIMPINAN TRANSFORMASIONAL TERHADAP KINERJA KARYAWAN DI PERUSAHAAN PERBANKAN SWASTA: PERAN MEDIASI KOMITMEN ORGANISASI - Hapsari, Bunga Barleana; Netania Emilisa; Tiara Puspa; fitriyani; Amalia Rosdiana (Universitas Trisakti, 2024)
This study aims to analyze the influence of job security and transformational leadership on job performance, with organizational commitment as a intervening variable. The approach used is descriptive quantitative with the research population consisting of employees working in the private banking sector. The sampling technique used in this study is purposive sampling with a sample size of 166 respondents. The results of the study reveal that job security and transformational leadership do not have an effect on job performance, while organizational commitment has a significant positive effect on job performance. Furthermore, job security and transformational leadership were found to have a significant positive influence on organizational commitment. Additionally, based on the results of the Sobel test, the researcher also found that organizational commitment can mediate the relationship between job security and transformational leadership on job performance. This study suggests expanding the number of respondents and conducting research in other sectors and different locations, as well as considering enriching the variables to obtain more varied and diverse findings.